An In vitro Study to Compare the Effect of Different Types of Tea with Chlorhexidine on Streptococcus mutans - Dona Elizabeth George; Roshan Shetty; Pooja j Shetty; Leslie Allan Gomes (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Tea is the second most commonly consumed beverage in the world after water. The leaf and bud of the plant Camellia sinensis produces tea. The different forms of tea are ‘non-fermented’ green tea, ‘semi-fermented’ oolong tea and ‘fermented’ black tea according to the manufacturing process. Streptococcus mutans is the main causative organism in dental caries and plaque formation. Aim: The present study was undertaken to determine the antibacterial effectiveness of aqueous and ethanol extracts of green tea, black tea and oolong tea against S. mutans in comparison with 0.2% chlorhexidine. Materials and Methods: An in vitro study was conducted to compare the effectiveness of aqueous and ethanol extracts of green tea, black tea and oolong tea with 0.2% chlorhexidine against S. mutans. Chlorhexidine 0.2% commercially available as mouthwash was used as such for comparison. The antimicrobial activity was determined using agar well diffusion method. About 50 µl of the aqueous and ethanol extracts of tea and 0.2% chlorhexidine were inoculated into the wells prepared on blood agar plates smeared with S. mutans. The agar plates were incubated for 24 hours after which the diameter of the zone of inhibition was measured. Analysis of Variance (ANOVA) followed by Tukey's post hoc test were used for statistical analysis. Results: The mean zone of inhibition of the aqueous extracts of green tea, black tea, oolong tea and chlorhexidine was found to be 16.33 mm, 10.33 mm, 19.66 mm and 22 mm respectively. The mean zone of inhibition of the ethanol extracts of green tea, black tea, oolong tea and chlorhexidine was found to be 14 mm, 9 mm, 20.66 mm and 22 mm respectively. The study result state that the inhibitory effect of chlorhexidine is almost similar to that of oolong tea followed by green tea and black tea. Conclusion: From the present study, it can be concluded that the aqueous and ethanol extracts of oolong tea showed highest antimicrobial activity compared to green tea and black tea.